Dynastischer Nachwuchs als Hoffnungsträger und Argument in der Frühen Neuzeit - Kommission, Historische; Kozmanová, Irena; van der Stehen, Jasper (Veröffentlichungen der Historischen Kommission zu Berlin, 2023)
This volume sheds light on the role played by progeny in maintaining dynasties in early modern royal courts. It attempts to break through the narrative of older research that saw dynasties as a series of male rulers. Instead, these contributions focus on how progeny were viewed at the time.